Validasi Dokumen Pengajuan Penelitian dan Pengabdian Masyarakat Universitas Nasional Menggunakan Metode Finite State Automata - Lili Dwi Yulianto; Windu Gata; Frieyadie; Dedi Dwi Saputra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Non-Deterministic Finite Automata (NFA), a form of Finite State Automata (FSA), is one method for validating research proposal documents in R&D and community service activities at national universities. To carry out these activities, it is necessary to monitor the research proposal documents submitted by lecturers/researchers, one of which is to validate the research proposal document, ensuring that it follows the guidelines and avoids plagiarism, as well as the theme's suitability with the research proposal document's contents. Members of the research team can only participate in one type of study: stimulation or competitive research. Reviewers can provide research members with notes and plagiarism information, as well as refuse to submit research proposals. If the research proposal document is approved by the reviewer, the research member will receive a research certificate and will be able to continue their research with full support from the national government.